The uniqueness of the European process of regional integration: institutional framework - Keino, Mikita M. (Journal of the Belarusian State University. International Relations, 2020)
The article covers supranational governance that relies on the well-built institutional structure of the EU and shows its peculiarity. It argues the fact that the EU can be perceived as a state in nature. The article also highlights the drawbacks in the formation and functioning of other regional integration associations such as ASEAN, NAFTA, and MERCOSUR. Good governance of the EU, remarkable economic results achieved by its members and the existence of strong and independent supranational institutions result in the EU uniqueness.